Filmic intertextualities: Cinema Libertad or the cinematographic thesis of Arturo Menéndez - Caña Jiménez, María del Carmen (2022)
The following pages revolve around Salvadoran Arturo Menéndez and seek to clarify the author’s cinematographic language based on the analysis of the intertextuality contained in Cinema Libertad (2009). In them I argue that, in Cinema Libertad, Menéndez proposes the thesis of what his production as a filmmaker will be, suggesting different ways for the aesthetic and ethical renewal of Salvadoran cinema. In Cinema Libertad Menéndez advocates for the creative capacity of cinema and the artistic freedom of the author while inviting us to reflect –albeit in a more intimate, critical and meditative way than more conventional audiovisual productions in the region– on the violence that still afflicts El Salvador.